MODEL AIICR (ANDALUSIAN-INSPIRED ISLAMIC CIVILIZATION RECONSTRUCTION): REKONSTRUKSI PERADABAN ISLAM INDONESIA MELALUI REFLEKSI HISTORIS ANDALUSIA - Novala Arum Salsabillah; Siti Fatimah Az-zahra; Kholid Mawardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic civilization in Indonesia faces various contemporary challenges, including socio-political polarization, the weakening of intellectual traditions, and declining social cohesion within a pluralistic society. This study aims to analyze the political dynamics, intellectual traditions, and social cohesion of Islamic Andalusia and to formulate the AIICR (Andalusian-Inspired Islamic Civilization Reconstruction) Model as a conceptual framework for reconstructing contemporary Indonesian Islamic civilization. This research employed a Systematic Literature Review (SLR) with a historical-critical approach. Data were collected from scholarly articles, books, historical documents, and relevant academic publications, then analyzed through thematic synthesis and historical interpretation. The findings indicate that the advancement of Andalusian civilization was supported by three main pillars: political stability, integrative intellectual traditions, and inclusive social cohesion. Conversely, its decline was driven by political fragmentation, the deterioration of intellectual culture, and weakened social solidarity. Based on these findings, this study proposes the AIICR Model, which consists of three interconnected pillars: inclusive political governance, integrative intellectual traditions, and social cohesion grounded in religious moderation and multicultural values. The model offers a conceptual framework for developing an advanced, inclusive, and sustainable Islamic civilization in contemporary Indonesia.